Transition-metal-catalyzed C–C bond macrocyclization via intramolecular C–H bond activation - Wang, Xiao. (2023)
Macrocycles are commonly synthesized via late-stage macrolactamization and macrolactonization. Strategies involving C–C bond macrocyclization have been reported, and examples include the transition-metal-catalyzed ring-closing metathesis and coupling reactions. In this mini-review, we summarize the recent progress in the direct synthesis of polyketide and polypeptide macrocycles using a transition-metal-catalyzed C–H bond activation strategy. In the first part, rhodium-catalyzed alkene–alkene ring-closing coupling for polyketide synthesis is described. The second part summarizes the synthesis of polypeptide macrocycles. The activation of indolyl and aryl C(sp2)–H bonds followed by coupling with various coupling partners such as aryl halides, arylates, and alkynyl bromide is then documented. Moreover, transition-metal-catalyzed C–C bond macrocyclization reactions via alkyl C(sp3)–H bond activation are also included. We hope that this mini-review will inspire more researchers to explore new and broadly applicable strategies for C–C bond macrocyclization via intramolecular C–H activation.